Just one wish - Rippin, Sally (Penguin, 2009)
"Penny (Little Pumpkin) has just moved to Australia and is starting a new school. But Betty, her cousin, is determined to make her life miserable. Penny has no idea why Betty is so against her, but because they are living with their cousins until they can set themselves up in their own house, and until her parents get jobs, Penny doesn't want to ruin the already shaky relations by complaining about Betty. Penny retreats to the art room every lunch to bury herself in her passion and talent - drawing - and there she finds an unlikely friend."--Provided by publisher